Architecting cloud‐enabled systems: a systematic survey of challenges and solutions. (13th May 2016) - Chauhan, Muhammad Aufeef; Babar, Muhammad Ali; Benatallah, Boualem
Summary: The literature on the challenges of and potential solutions to architecting cloud‐based systems is rapidly growing but is scattered. It is important to systematically analyze and synthesize the existing research on architecting cloud‐based software systems in order to build a cohesive body of knowledge of the reported challenges and solutions. We have systematically identified and reviewed 133 papers that report architecture‐related challenges and solutions for cloud‐based software systems. This paper reports the methodological details, findings, and implications of a systematic review that has enabled us to identify 44 unique categories of challenges and associated solutions for architecting cloud‐based software systems. We assert that the identified challenges and solutions classified into the categories form a body of knowledge that can be leveraged for designing or evaluating software architectures for cloud‐based systems. Our key conclusions are that a large number of primary studies focus on middleware services aimed at achieving scalability, performance, response time, and efficient resource optimization. Architecting cloud‐based systems presents unique challenges as the systems to be designed range from pervasive embedded systems and enterprise applications to smart devices with Internet of Things. We also conclude that there is a huge potential of research on architecting cloud‐based systems in areas related to green computing, energy efficient systems, mobile cloud computing, and Internet of Things. Copyright © 2016 John Wiley & Sons, Ltd.